Edukasi Pengelolaan Sampah Rumah Tangga di Kabupaten Bantul DIY - Ruliyandari, Rochana; Fathin Nufus, Karine; Huzaifi Ahmad, Aditama; Indi Dini Azhar Hidayat, Gt; Talib , Zaini; Martha Naura , Hasna; Maisun Saffanah , Amadini (COVIT (Community Service of Tambusai), 2023)
Waste that is not managed properly will cause environmental and public health problems. Dangerous diseases that can arise from waste include diarrhea, dengue fever, typhus, and so on. Environmental problems that also arise from waste are air pollution through odors that interfere with breathing and water pollution originating from leachate resulting from waste generation that enters the ground, thereby contaminating groundwater and/or surrounding water sources. Compost is the result of fermenting organic materials such as plant leaf clippings, vegetables, fruits, organic waste, livestock manure, and other materials. Compost can be used as a natural fertilizer and to restore soil nutrients that may be lost during harvest and due to erosion. This activity aims to provide knowledge about overcoming environmental health problems in RT 23 and 24 Wonocatur with activities in the form of counseling and training in making loseda. Service Activities in Rt 23 and 24 Wonocatur Using Descriptive Quantitative Methods, Using a Cross Sectional Approach, Data collection using questionnaires prepared online by the campus in collaboration with the Banguntapan III Health Center RT 23 and 24, Wonocatur Hamlet, Banguntapan Village, Banguntapan District, Bantul Regency, DI Yogyakarta Province. There are problems in RT 23 and 24 Wonocatur, namely environmental health problems. Some residents do not have closed wet (organic) waste bins. To overcome these problems, counseling and training on waste management is carried out using the loseda method. The knowledge of the residents of RT 23 and 24 during the posttest increased after being given counseling and training. Keywords: organic waste, counseling, processing, training